Boundary-Nonregular Functions in the Disc Algebra and in Holomorphic Lipschitz Spaces - Bernal-González, L.; Bonilla, A.; López-Salazar, J.; Seoane-Sepúlveda, J. B. (Mediterranean journal of mathematics, 2018)
We prove in this paper the existence of dense linear subspaces in the classical holomorphic Lipschitz spaces in the disc all of whose non-null functions are nowhere differentiable at the boundary. Infinitely generated free algebras as well as infinite dimensional Banach spaces consisting of Lipschitz functions enjoying the mentioned property almost everywhere on the boundary are also exhibited. It is also investigated the algebraic size of the family of functions in the disc algebra that either do not preserve Borel sets on the unit circle or possess the Cantor boundary behavior on the disc.